Financing Democracy or Corruption? Political Party Financing in the EU's Southeastern and Eastern Member States - Ada-Iuliana Popescu (CES Working Papers, 2015)
Fighting public-sector corruption has become a priority for most governments and international organizations. The public sector is the source of many benefits. Realizing improper private gains from these benefits has long been the core definition of corruption. As the public sector grows and expands its activities, the complexity of its activities also increases. The opportunities for improper private gains grow, too. Therefore, not surprisingly, the EU admits that the public sector, including political parties and public administrations, are especially vulnerable to corruption. Political parties, for instance, depend on the funding destined for their capability to win elections and otherwise to influence public policies. In turn, this dependency creates opportunities for a variety of corrupt activities. Ensuring that campaign funding promotes democracy and not corruption requires well-crafted, vigorously enforced laws. This article analyzes the legal framework of political party financing in the Eastern and South-eastern European EU member states, in order to assess how well it works in preventing political party corruption.
Keywords: D73; H83; K42; 330; public-sector corruption; political party; corrupt practices; anti-corruption initiatives